Financial Literacy Externalities - Haliassos, Michael; Jansson, Thomas; Karabulut, Yigitcan (Review of Financial Studies, 2020)
[We use unique administrative data and a quasi-field experiment of exogenous allocation in Sweden to estimate medium-and longer-run effects of peoples’exposure to financially literate neighbors on their financial behavior. We contribute evidence of (1) a causal impact of exposure and of a social multiplier of financial knowledge and (2) unfavorable distributional aspects of externalities. Exposure promotes saving in private retirement accounts and stockholding, especially when neighbors have economics or business education, but only for educated households and for substantial interaction possibilities. Findings point to a transfer of knowledge rather than mere imitation or effects through labor, education, or mobility channels.]